LINC00470 promotes tumour proliferation and invasion, and attenuates chemosensitivity through the LINC00470/miR‐134/Myc/ABCC1 axis in glioma. Issue 20 (11th September 2020) - Wu, Changwu; Su, Jun; Long, Wenyong; Qin, Chaoying; Wang, Xiangyu; Xiao, Kai; Li, Yang; Xiao, Qun; Wang, Junquan; Pan, Yimin; Liu, Qing
Abstract: Glioma is the most common primary malignant tumour in the brain; temozolomide (TMZ) is the most prevalent chemotherapeutic drug currently used to combat this cancer. We reported previously that the long intergenic non‐protein coding RNA 470 (LINC00470) is a novel prognostic biomarker for glioma and promotes the tumour growth in an intracranial transplantation mouse model. However, the effects of LINC00470 on glioma cell proliferation, invasion and TMZ chemosensitivity, as well as its molecular mechanism, remain unclear. In this study, we found elevated expression levels of LINC00470 and MYC in glioma tissues and cells and decreased expression of microRNA‐134 (miR‐134). Functional studies have shown that LINC00470 promotes proliferation and invasion, and attenuates chemosensitivity of glioma cells, while miR‐134 exerts the opposite effect. In the rescue experiments, the tumorigenic effect of LINC00470 was offset by miR‐134. In the mechanism study, we found that LINC00470 was a competitive endogenous RNA (ceRNA) of miR‐134 and that miR‐134 can directly target MYC and negatively regulate its expression. Furthermore, MYC was positively correlated with ATP‐binding cassette subfamily C member 1 (ABCC1) expression in glioma cells and MYC up‐regulated ABCC1 expression. Further studies found that LINC00470 regulated MYC by sponging miR‐134 to regulate the expression of ABCC1. We concluded that LINC00470 promoted the expression of MYC and ABCC1 by suppressing miR‐134, thus promoting glioma cell proliferation and invasion, and attenuating TMZ chemosensitivity. Moreover, the LINC00470/miR‐134/MYC/ABCC1 axis constitutes a potential therapeutic target.